2012
DOI: 10.1111/j.1600-0609.2012.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone health in persons with haemophilia: a review

Abstract: Bone density is a measure of equilibrium between bone formation and bone resorption; any imbalance in these two processes might lead to osteopenia and osteoporosis. Osteoporosis in general has been considered to be an important cause of morbidity in both men and women and more so in haemophilia and other bleeding disorders. Specific triggering factors in persons with haemophilia (PWH) are abnormal liver function because of viral infection, bleeding and inflammation, lack of physical and athletic activities, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
(74 reference statements)
1
20
1
2
Order By: Relevance
“…In normal healthy people, BMI and BMD are known to be related. While some studies have also confirmed the existence of such a relationship in haemophilia patients, others have reached the opposite conclusion . Our results indicated a statistically significant positive correlation between BMI and femoral neck, lumbar spine and total hip BMD.…”
Section: Discussioncontrasting
confidence: 51%
“…In normal healthy people, BMI and BMD are known to be related. While some studies have also confirmed the existence of such a relationship in haemophilia patients, others have reached the opposite conclusion . Our results indicated a statistically significant positive correlation between BMI and femoral neck, lumbar spine and total hip BMD.…”
Section: Discussioncontrasting
confidence: 51%
“…Bone disease in haemophilia has been attributed to bleeding sequelae from chronic inflammation and decreased weight‐bearing activity from painful and debilitating haemarthroses (Ghosh & Shrimati, ). Chronic hepatitis C and HIV infections are associated with poor bone health and have a high incidence in the haemophilia population secondary to past exposure to contaminated blood products (Lo et al , ).…”
Section: Haemophilia Cohort Baseline Characteristicsmentioning
confidence: 99%
“…To the editor: Ghoshy et al in their recent review in European Journal of Haematology (1) tried to present data about the prevalence of low bone mineral density (BMD) in patients with haemophilia A and B and analyse the pathophysiology of this entity proposing appropriate management. The authors report data of small studies and refer mainly to the association of low BMD with hepatitis C (HCV) and human immunodeficiency virus (HIV) infections and their treatment (interferona, antiretroviral therapy).…”
Section: Bone Disease In Patients With Haemophilia What Is True?mentioning
confidence: 99%